Relevansi Nilai Pendidikan Karakter dalam Geguritan Suddhamala untuk Meningkatkan Mutu Pendidikan di Indonesia - Kadek Dedy Herawan; I Ketut Sudarsana (UHN IGB Sugriwa Denpasar, 2017)
Geguritan as one of the traditional literature is widely used by the authors to pour the brilliant idea of character education through the medium of art language that is strung together based on the diction that is very ungrateful. Through geguritan, a person has indirectly got a character education that is able to build a good mindset, words and deeds. The development of technology and communication in this era of globalization has gradually eroded the interest of teenagers to know and learn traditional literature. Learners are more interested in the things that smelled of technology, especially social media and override traditional literature, one of which is literature geguritan. Geguritan Suddhamala as one of literature geguritan loaded with character values that can be used as guidance in improving the quality of education quality. The relevance of character education in Suddhamala geguritan is divided into three namely divinity / humanity, humanity, and environment. The entire field of character has relevance to efforts to improve the quality of education in Indonesia.